2013
DOI: 10.1021/ja409241h
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)/ABNO-Catalyzed Aerobic Alcohol Oxidation: Alleviating Steric and Electronic Constraints of Cu/TEMPO Catalyst Systems

Abstract: Cu/TEMPO catalyst systems promote efficient aerobic oxidation of sterically unhindered primary alcohols and electronically activated substrates, but they show reduced reactivity with aliphatic and secondary alcohols. Here, we report a catalyst system, consisting of ((MeO)bpy)Cu(I)(OTf) and ABNO ((MeO)bpy = 4,4'-dimethoxy-2,2'-bipyridine; ABNO = 9-azabicyclo[3.3.1]nonane N-oxyl), that mediates aerobic oxidation of all classes of alcohols, including primary and secondary allylic, benzylic, and aliphatic alcohols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
233
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(244 citation statements)
references
References 38 publications
3
233
0
8
Order By: Relevance
“…In particular, they have proven excellent reagents for the selective oxidation of primary alcohols, [1][2][3][4][5] secondary alcohols, 6,7 primary amines, 8 and the -oxyamination of aldehydes. 9 More recently, TEMPO has also found use in the depolymerization of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they have proven excellent reagents for the selective oxidation of primary alcohols, [1][2][3][4][5] secondary alcohols, 6,7 primary amines, 8 and the -oxyamination of aldehydes. 9 More recently, TEMPO has also found use in the depolymerization of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of hydrogen atoms at the ␣-carbon atom in sterically hindered N-oxy radicals such as TEMPO prevents their degradation via elimination reactions. More recently, attention has been drawn to the use of sterically unhindered nitroxyl radicals such as AZADO [75,76] and ABNO [77,78], and derivatives thereof (Fig. 8), which possess ␣-hydrogens but are nonetheless stable toward elimination because the resulting double bond would be formed at a bridgehead and, hence, violate Bredt's rule [79].…”
Section: Stable N-oxy Radicals As Organocatalystsmentioning
confidence: 99%
“…Furthermore, there are many oxidation catalysts prepared by employing noble metals, such as gold [16][17][18][19][20][21], palladium [22][23][24][25], platinum [26,27], rhodium [28,29], and ruthenium [30,31], which have been extensively utilized for the aerial oxidation of alcohols with high catalytic performances. Consequently, a significant effort has been made in order to explore eco-friendly and low cost catalysts 2 Advances in Materials Science and Engineering such as nonnoble metals like copper [32][33][34], cobalt [35][36][37], nickel [38][39][40], iron [41,42], vanadium [43], silver [44], chromium [45,46], molybdenum [47,48], rhenium [49], and zinc [50][51][52] for aerobic oxidation of alcohols. In addition, it has been extensively reported that the catalytic activity of mixed metal oxide nanoparticles catalysts enhanced remarkably upon doping with other metals probably due to the extremely high surface area of metal nanoparticles [53,54].…”
Section: Introductionmentioning
confidence: 99%